Deformable image registration applied to lung SBRT: Usefulness and limitations. (December 2017) - Sarrut, David; Baudier, Thomas; Ayadi, Myriam; Tanguy, Ronan; Rit, Simon
Highlights: Review the status of DIR for lung RT, its main applications, its associated uncertainties and its limitations. Large bibliography, classified according to the applications. Focus on the application of DIR in clinic. Abstract: Radiation therapy (RT) of the lung requires deformation analysis. Deformable image registration (DIR) is the fundamental method to quantify deformations for various applications: motion compensation, contour propagation, dose accumulation, etc. DIR is therefore unavoidable in lung RT. DIR algorithms have been studied for decades and are now available both within commercial and academic packages. However, they are complex and have limitations that every user must be aware of before clinical implementation. In this paper, the main applications of DIR for lung RT with their associated uncertainties and their limitations are reviewed.